Leadership Style of Women in the Bureau of Government and People's Welfare Secretariat of the Provincial Government of Gorontalo - Grace Oktovina Maskikit; Lisda Van Gobel; H.Rukiya Nggilu (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the Leadership Style of Women in the Bureau of Government and Welfare at the Regional Secretariat of Gorontalo Province. With the research sub-focus, namely telling style, selling style, participating style, and gelegating. This research uses a qualitative descriptive research type. Data collection techniques used are: Observation techniques, interviews and secondary data recording. In accordance with the type of research used, the data analysis technique used is a qualitative analysis technique. The results of the study show that seen from the telling style (appeals) it is not optimal, because the orders or appeals of female leaders to employees have not yielded maximum results. As for the things suggested in this study, namely the need for leaders in carrying out their duties to always remind subordinates, so that organizational tasks can be carried out in accordance with predetermined targets.